Letter from W. A. Wildhack to Arnold O. Beckman - Wildhack, W. A. (1950)
The letter concerns importation of spectrophotometers into Germany and France, the Economic Cooperation Administration (ECA), and post-war atomic energy restrictions.
Keywords: Imports; Scientific apparatus and instruments; International trade; Allied High Commission for Germany; Germany; Beckman Instruments, Inc.; United States. Economic Cooperation Administration